Audial Kinetics and the Disembodied Voice - Eadie, Jimmy (Springer, 2022)
This paper will explore the basic relationships between disembodied speech and aesthetic experience in sound art through an exploration of two original artworks, Rehearsal (2018) and Souvenir Redux (2019). The emphasis here is on how these works connect individuals across a variety of listening contexts, as well as the aesthetic and social implications revealed and communicated by the installation experience. The premise is that while sound installation art is a tangible object, it emphasizes a dislocated and dynamic sensory experience through a complex combination of aural, kinetic, and visual experience. The dissociation of sight and sound promotes a particular type of listening in which we can explore the inherent dimensions of sound and discover that a sound’s emotional, physical, and artistic value is found not just in its context or meaning, but also in its acoustic qualities of timbre and texture. In many respects, the works presented here are a meta-referential exploration of sonic-space. Furthermore, the objective is to create an immersive audio envi- ronment that takes the listener into the constructed sonic world, where the dis- embodied voice thematically develops over time. The work’s disconnected sound world and heightened sense of sonic perspective are explored using low and high- fidelity audio aesthetics, as well as media-specific self-reference. While the works include conversation fragments, it is not driven by a textual narrative but rather seeks to evoke experiences similar to those elicited by hearing poetry read aloud. Ultimately, these soundscape works integrate text, field recordings, and music, all of which play a part and work in tandem to provide each listener with a particular personal experience.
Interactivity and Game Creation
EAI ArtsIT 2022 - 11th EAI International Conference: ArtsIT, Interactivity & Game Creation
Keywords: sound art; disembodied voice; kinetics; installation; listening